Take 4x + 2 from 8x + 5.

Question

Asked 6/30/2016 11:01:22 PM

Updated 7/1/2016 8:09:51 AM

1 Answer/Comment

This answer has been confirmed as correct and helpful.

s

= (y^4/y+1) - (1/y+1)

=y^3 - y^2 + y - 1

= 6x^2 - 3x +10x - 5

= 6x^2 +7x - 5

The middle term of the product is 7x.

Question

Asked 6/30/2016 11:01:22 PM

Updated 7/1/2016 8:09:51 AM

1 Answer/Comment

This answer has been confirmed as correct and helpful.

Rating

There are no new answers.

Find the product.
2y 2(3x + 5z) **Weegy:** 2y^2(3x + 5z) = 2y^2*3x + 2y^2*5z = 6xy^2 + 10y^2z **User:** Find the product.
x 3(x 2 + 5x + 1) **Weegy:** x^3(x^2 + 5x + 1) = x^5 + 5x^4 + x^3 (More)

Question

Updated 6/24/2016 8:35:05 AM

0 Answers/Comments

Fully factor x(2x + 3) + (x - 3)(x - 4)

Question

Updated 7/1/2016 9:23:01 AM

1 Answer/Comment

x(2x + 3) + (x - 3)(x - 4) = 3x^2 - 4x + 12

Added 7/1/2016 9:22:58 AM

This answer has been confirmed as correct and helpful.

7,529,536^1/3

Question

Updated 7/4/2016 1:46:13 AM

1 Answer/Comment

7,529,536^1/3

= 7,529,536/3

= 2509845.33

= 7,529,536/3

= 2509845.33

Added 7/4/2016 1:46:13 AM

This answer has been confirmed as correct and helpful.

33,066,159

questions answered

There are no comments.